Sistem Pendukung Keputusan Penentuan Kelayakan Pengajuan Kredit Motor Berbasis Simple Additive Weighting (SAW): Study Kasus UD. Putra Mandiri Motor - Khoirudin, Dhimas Hafidh; Anam, Chairul; Khafidhoh, Nur (Exact Papers in Compilation (EPiC), 2022)
Motorcycles are a popular transportation in Indonesia, besides because the price is quite affordable time efficiency is also a benchmark for why Indonesians prefer motorcycles than any other means of transportation. To lighten the burden of purchasing a motorcycle, it is necessary to make purchases on credit. However, bad credit is not uncommon for some of the problems that arise. Therefore, in this study will be applied to a decision support system using Simple Additive weighting method (SAW) to assess the credit application. SAW method is the simplest method of MADM because the basic concept SAW method is to find the sum of the weighted performance rating for each alternative on all attributes. Values obtained criteria of each customer or alternatively along the desired selection of motorcycles will be entered into the decision support system and will be calculated. Then the system will display the results of these calculations and shows the feasibility of the credit application. In this decision support system using five criteria, personality of the installment payment of financial institutions, income, business or employment status, home status and dependents. . Keywords: Credit, Decision Support System, Simple Additive Weighting